2014
DOI: 10.3906/sag-1304-38
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic Castleman disease

Abstract: Isolation and identification of Avibacterium paragallinarum, the causative agent of infectious coryza, is considered a challenging task in laboratories with limited specialties. In the present study, 14 commercial layer fowls showing the typical symptoms of infectious coryza were subjected to primary isolation followed by polymerase chain reaction confirmation of suspect colonies (culture-PCR). Direct PCR assays on infraorbital sinus swab samples were also carried out. Thirty-five suspected cases of infectious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…HV-MCD is a relatively rare clinical type, especially those cases with pulmonary involvement, and case has been reported in the literature mentioned the details of respiratory lesion was rare [2] so far. However, the details of pulmonary involvement were not descripted in those reported cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HV-MCD is a relatively rare clinical type, especially those cases with pulmonary involvement, and case has been reported in the literature mentioned the details of respiratory lesion was rare [2] so far. However, the details of pulmonary involvement were not descripted in those reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…4 cases of HV-MCD involving the lungs were reported previously [2,29], but chest CT, blood gas analysis and lung function results were not described in detail. HV-MCD is a rare type of CD.…”
Section: Discussionmentioning
confidence: 99%
“…However, in any case, the findings are not specific for CD, making it very difficult to reach the diagnosis by radiological findings alone. Moreover, from the reports so far, definitive diagnosis by preoperative biopsy seems difficult [912]. Similarly, the preoperative diagnosis of our case could not be made because of insufficient biopsy specimens for the pulmonary hilar mass.…”
Section: Case Presentationmentioning
confidence: 76%
“…They reported that disease progression was noted at four years after surgery in one patient and, in another patient, complete resection was performed eight years after an initial biopsy and observation following the onset of symptoms [2]. Moreover, Biçakçioğlu et al reported that 17 of the 19 CD cases, including seven cases in the pulmonary hilum, in which surgery was performed were localized, and that 15 cases in which complete resection was performed had no recurrence [12]. Therefore, the recommended treatment strategy for localized HV type CD is complete resection.…”
Section: Case Presentationmentioning
confidence: 99%
“…2,3 However, because of local infiltration and excessive vascularisation, surgery is often associated with severe haemorrhage or a failure to achieve complete resection. 4,5 Here, we describe a case of rapid recovery from the surgical resection of giant mediastinal lymph node hyperplasia.…”
Section: Introductionmentioning
confidence: 98%